Prevalence of Self-Medication among Urban Population Participating Community Pharmacies - Khan, Kayamkani Abedulla (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: Self-medication is defined as the individuals who used to treat self-recognized symptoms or illnesses using and selecting traditional, herbal medicine products. Self-medication permits the consumer or patient to take an active role. However, it is not a completely safe health character, particularly in the irresponsible or unreliable practice cases. Incorrect self-diagnosis, adverse reactions, masking of severe disease, incorrect dosage, and incorrect choice of therapy, drug interactions, dependence, and abuse are the potential risks of self-medication. Objective: The objective of the study was to determine the prevalence of self-medication in urban population and to identify any factors contributing to self-medication in relation to assess the attitude, perception, and knowledge of consumers toward self-medication. Materials and Methods: Our study was a cross-sectional survey which was conducted over 12 weeks from the month February to May in Jeddah city, K.S.A. Self-administered, validated questionnaire was used to collect the data and questionnaire was designed by reviewing the available research literature. It was designed in the English and Arabic language. Results: A total of 1036 peoples participated in the survey. Most responders were female (59.26%) and the males were 40.73%, the participants were predominantly in the age group of 25–40 years which were 38.41%. About 94.11% of participants are answered in Arabic and 5.88% were answered in English language. The most common medications consumed without prescriptions were painkillers (93.05%). The reasons for self-medications were health problems which were not serious (67.18%). Conclusion: In the study of rational drug use, assessment of self-medication is most important element. The observation of this research should form the basis for future interventional plans to increase benefits and decrease risks. In Saudi Arabia, community pharmacies have the potential to make a great impact in ensuring medicines which are properly utilized.